THE EFFECT OF INTEGRATED SCIENCE WORKSHEETS CONTAINING NEW LITERACY THEME OF RESPIRATORY HEALTH AND EXCRETION ON THE STUDENT’S COMPETENCE IN SMPN 25 PADANG - Erna Indah Kurniawati; Asrizal Asrizal; Yurnetti Yurnetti (Universe, 2020)
In the 2013 curriculum, science learning was implemented based on integration to improve student competency. However, the real conditions in schools show that the integration of learning materials in the worksheet and literacy integration that were applied was in the low category. The solution to overcome this problem is to use a integrated science worksheet containing new literacy theme of respiratory health and excretion. The purpose of this research was to investigate the effect of integrated science worksheet containing new literacy theme of respiratory health and excretion on the students competence in SMPN 25 Padang. This type of research used quasi experimental design with randomized control group posttest only design. The instrument used in this research consisted of observation sheet for attitude competency, written test for knowledge competency, and performance assessment for skill competency. Based on the analysis that has been done, it can be stated that the use of integrated science worksheet containing literacy new has a significant influence on student competence. These results indicate that the use of integrated science worksheet containing new literacy theme of respiratory health and excretion is effectively applied in schools.